Folate status and intake of tribal Indian adolescents aged 10 to 17 years - Jani, Rati; Salian, Nisha; Udipi, Shobha; Ghugre, Padmini; Lohia, Neha; Haas, Jere D.; Boy, Erick (SAGE Publications, 2015)
Adequate folate intake and levels are advisable throughout life but are of particular importance during adolescence, a period of rapid growth. However, folate insufficiency in economically deprived Indian adolescents is understudied.This cross-sectional study examined the prevalence of folate deficiency and adequacy of folate intake of 224 tribal Indian adolescents (10 to 17 years of age). The secondary aim was to study the association between anemia status and folate status.Radioimmunoassay, multiple-pass 24-hour dietary recall, and HemoCue were used to measure red blood cell (RBC) folate, folate intake, and anemia status, respectively.The geometric mean (95% CI) RBC folate concentration (nmol/L) was 360.2 (329.7 to 393.6), and the mean ± SD folate intake (μg/day) and hemoglobin level (g/L) were 159.9 ± 44.7 and 125.4 ± 13.0, respectively. Almost half of boys and girls aged 10 to 12 and 13 to 15 years and 66.7% of girls aged 16 to 17 years were deficient in RBC folate (< 340 nmol/L). The mean ± SD folate intake (μg/day) of girls (139.4 ± 34.5) was lower than that of boys (173.8 ± 45.5) ( p < .001). With respect to adequacy of folate intake, a greater proportion of girls in the age group of 13–15 years (78.5% vs 38.6%, p < 0.001) and 16–17 years (100.0% vs 76.9%, p = 0.04) had intakes below their Recommended Dietary Allowance (RDA). No association was observed between folate intake and RBC folate deficiency or between anemia status and RBC folate deficiency.Folate insufficiency was widespread in tribal Indian adolescents. There is an urgent need to develop culturally sensitive strategies for improvement.